MANAJEMEN MUTU KESEHATAN DAN LINGKUNGAN - Dian Purnamasari; Sujianto ' (Universitas Riau, 2013)
This study aims to determine theimplementation of quality management in the Unit of Health and Environment Laboratory RiauProvince. This study uses a quantitative approach to survey method-explanatory. At this stage ofthe analysis used by analytical approach and combine it with the description of the analysis usingstatistical analysis to determine the strengths and weaknesses of the relationship between thevariables affecting this study. The results demonstrate the strength of relationship qualitymanagement obtained a total score of 872. Thus, it can be seen that the quality managementassessed both at UPT. Environmental Health Laboratory and Riau Provincial Health.